PEREMPUAN MENGGUGAT DISKRIMINASI: PEMBARUAN HUKUM KELUARGA DALAM NARASI YURIDIS MAHKAMAH KONSTITUSI - Imam - Mustofa; Wildani Hefni; Mufliha Wijayati (PSGA LP2M IAIN Pontianak, 2021)
ABSTRACT The polemic of discrimination against women seems to be endlessly debated. The strong conservatism of discriminatory policies against women has led to the practice of identity politics in regulations, including law No.1/1974 on marriage. Since the existence of the Constitutional Court in 2003 until now, there have been two decisions that annulled the provisions of the marriage law due to eliminate and discriminate against the right of women. This study examines the gender equality lawsuits of women in the Constitutional Court decisions in various legal narratives in Indonesia. Based on the content analysis approach, the result of this study conclude that two decisions of the Constitutional Court No. 46./PUU-XIII/2010 and No. 22 / PUU-XV / 2017 has a significant impact on increasing the dignity and status of Indonesian women. An indication of this is the elimination of discrimination in the form of equal rights between men and women as an effort to reform family law in Indonesia with gender equity. Keywords: Women, Gender Discrimination, Constitutional Court, Reform of Family Law ABSTRAK Polemik diskriminasi terhadap perempuan menjadi isu yang tak pernah selesai diperbincangkan. Kuatnya konservatisme kebijakan yang diskriminatif terhadap perempuan menyuburkan praktik politik identitas dalam regulasi, termasuk dalam Undang-undang No. 1 tahun 1974 tentang perkawinan. Sejak keberadaan Mahkamah Konstitusi tahun 2003, sampai saat ini sudah dua putusan Lembaga Tinggi Negara tersebut yang menganulir ketetapan dalam pasal-pasal Undang-undang perkawinan karena terbukti bias gender dan menimbulkan diskriminasi bagi kaum perempuan. Artikel ini mengkaji gugatan kesetaraan gender dari kaum perempuan dalam putusan-putusan Mahkamah Konstitusi yang menggugat hak-hak diskriminatif dalam pelbagai narasi hukum di Indonesia. Dengan menggunakan analisis isi, studi ini menyimpulkan bahwa narasi yuridis Putusan Mahkamah Konstitutusi No. 46./PUU-XIII/2010 dan putusan No. 22/PUU-XV/2017 berdampak signifikan bagi peningkatan harkat dan martabat perempuan Indonesia. Indikasi dari hal tersebut adalah penghapusan bentuk diskriminasi berupa kesataraan hak antara laki-laki dan perempuan sebagai upaya pembaruan hukum keluarga di Indonesia yang berkeadilan gender. Kata kunci: Perempuan, Diskriminasi Gender, Mahkamah Konstitusi, Pembaruan Hukum Keluarga